CLINICAL USE OF ENZYMES IN PEDIATRIC GASTROENTEROLOGY - А.N. Surkov (Вопросы современной педиатрии)
High incidence of various pediatric gastroenterologic diseases including congenital still remains an important issue for a Russian healthcare. The latter may be attended by relative or total excretory pancreatic failure with the following symptoms: stool abnormalities, abdominal pain, meteorism, weakness, low appetite and physical exercise, weight reduction and growth retardation. Pancreatic enzymes that contribute to protein, lipids and carbohydrates digestion are often used as a replacement therapy in pediatric care. Nowadays there is a plenty of choice among enzymatic medications. However, not all aforesaid medications can ensure adequate replacement treatment especially in children with chronic pancreatic failure. That is why among agents of choice are modern and highly effective microgranulated encapsulated pancreatines. For example Micrazim.Key words: children, pancreas, pancreatic failure, enzymotherapy.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2011; 10 (3): 114–118)